Analisis Faktor-Faktor Kesulitan Membaca pada Peserta Didik dan Upaya Penanganannya di SDN Pucangsewu - Herawati, Annisa; Wahyu Prakosa, Aldiansyah; Martadinitasari, Afifah Intan; Agustina, Fadhilla Cindy; Romadhana, Yudha Suci; Erviana, Lina (PGSD STKIP PGRI Pacitan, 2025)
Students who have difficulty reading, it turns out that not only students in lower grades, but students in higher grades also still have some children who have difficulty reading. The purpose of this study, among others, researchers want to know the factors that influence students' reading difficulties at SDN Pucangsewu and the efforts made by teachers to overcome these problems. The method used in this study is qualitative descriptive research. Qualitative descriptive research is used to understand the subjects studied about the reading difficulties experienced by the subjects. Based on the results of observations and interviews that have been conducted, it was identified that subjects who had difficulty reading were in 3 classes, namely class III as many as 2 children, class IV as many as 2 children, and class VI as many as 1 child. There are several factors that influence reading difficulties in students, including internal factors and external factors of students.